Detection of Circulating Tumor Cells in Resectable Pancreatic Ductal Adenocarcinoma: A Prospective Evaluation as a Prognostic Marker - Song, Byeong Geun; Kwon, Wooil; Kim, Hyemin; Lee, Eun Mi; Han, Young Min; Kim, Hongbeom; Byun, Yoonhyeong; Lee, Kyung Bun; Lee, Kwang Hyuck; Lee, Kyu Taek; Lee, Jong Kyun; Jang, Jin-Young; et al. (Frontiers in Oncology, 2021)
Circulating tumor cells (CTCs) are useful biomarkers of many solid tumors, but are infrequently detected in early stage pancreatic ductal adenocarcinomas (PDACs). The first drainage of pancreatic venous blood flow come to portal vein and pass through the liver, and they finally go out for peripheral blood. We thought that comparing CTCs from portal vein and peripheral blood could enable us to understand the clinical meaning of CTCs from each different site in PDACs. Therefore, we aimed to determine 1) whether CTCs could be reliably identified in early stages (operable) of PDACs, 2) if there are any differences in the detected number of CTC in portal vein blood and peripheral blood, and 3) whether CTCs can be sensitive biomarkers for the prognosis of resectable PDAC patients. Newly diagnosed PDAC patients who underwent operation with curative intention between 2013 and 2015 were prospectively enrolled. Blood draws from portal and peripheral vein ran through the microfabricated porous filter, and anti-epithelial cell adhesion molecule (EpCAM) and anti-Plectin-1 antibodies were used for CTC identification. Baseline clinical characteristics, tumor characteristics, treatment, and clinical outcomes were assessed. The clinical stages of the 32 enrolled patients were as follows: IA/ IB 1 (3.1%); IIA 9 (28.1%); IIB 17 (53.1%); III 5 (15.6%). Twenty-seven patients (84.4%) received R0 resection, while five patients (15.6%) received R1 resection. EpCAM+ CTCs were detected in 20 portal blood (62.5%) and 22 peripheral blood (68.8%). Plectin-1+ CTCs were identified in 14 portal blood (43.8%) and 16 peripheral blood (50%). Plectin-1-expressing CTCs were picked from CTC platform (microfabricated porous filter) and we could find out all KRAS mutation. Patients with detectable EpCAM+ CTC less than one in peripheral blood showed longer overall survival (OS) compared to patients with detectable CTCs more than one (35.5 months vs. 16.0 months). EpCAM and Plectin-1 successfully identified CTCs at the early stage of PDACs. Also, the number of CTCs could be a prognostic marker for survival in resectable PDACs.